Direct Syn Addition of Two Silicon Atoms to a C≡C Triple Bond by Si−Si Bond Activation: Access to Reactive Disilylated Olefins. (23rd January 2017) - Ahmad, Maha; Gaumont, Annie‐Claude; Durandetti, Muriel; Maddaluno, Jacques
Abstract: A catalytic intramolecular silapalladation of alkynes affords, in good yields and stereoselectively, syn ‐disilylated heterocycles of different chemical structure and size. When applied to silylethers, this reaction leads to vinylic silanols that undergo a rhodium‐catalyzed addition to activated olefins, providing the oxa‐Heck or oxa‐Michael products, depending on the reaction conditions.